Perancangan Antena Mikrostrip Multiband Bentuk Segi Empat 2 Patch Menggunakan Gabungan Metode Array Dan Slot - Junas Haidi; Alex Surapati; Tri Riski Pahlovi (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2017)
Antenna is the most important thing in wireless technology. The technology of communication in this era does not only work on only one frequency, but it has many work frequency. In this research, the method that is used to create the antenna works in Multiband by using an array and slot method. Based on the result of this research, quadrilateral microstrip antenna by using 2 patches has a resonant frequency of 1,3 GHz, 1,8 GHz, 2,4 GHz, and 2,8 GHz. From the measurement results that is done, all antennas that resonate at that frequency has met the antenna standard which is the value of return loss less than -10 dB and VSWR less than 2, so that the antenna that has been made can work well in accordance with the function of the antenna. The slot method used in the design of microstrip antenna operates to add up the resonant frequency of the antenna and improve the value of return loss. Meanwhile, the array method that is used can add up the resonant frequency in microstrip antenna. By combining both methods in the design of quadrilateral microstrip antenna, it will generate a multiband antenna resonance frequency.